Achados do estudo eletrofisiológico em pacientes com miocardiopatia chagásica e síncope com padrão eletrocardiográfico de bloqueio de ramo e/ou bloqueio divisional - Dreicon, Alexia Hallack (2021)
Background: Hypertrophic cardiomyopathy (HCM) is considered the most common genetic cardiovascular disease and has a prevalence of its phenotype in the general population of approximately 0.2%. In its physiopathology, ventricular hypertrophy promotes structural and functional modifications, such as fibrosis focus and microvascular ischemia, diastolic dysfunction and atrial enlargement, which predisposes the development of atrial fibrillation (AF). This arrhythmia reaches the prevalence of about 20-25% of patients with HCM and is associated with adverse consequences, including systemic cardioembolic stroke and progressive symptoms of heart failure, negatively impacting morbidity and mortality and quality of life. In general, it manifests oligosymptomatically and only appears in situations of complications. Thus, currently studies aim to find clinical, electrocardiographic or echocardiographic predictors for the development of AF in patients with HCM, to enable their early detection and rapid therapeutic intervention. Methods: We have assessed the left atrial function by using three-dimensional echocardiography and speckle tracking technique in 53 patients with HCM, 25 of them had paroxysmal AF (mean age 61,7 ± 9,9 years; 56% were women), who were compared with 28 patients in control group (mean age 60,5 ± 10 years; 53,6% were women) which were matched especially by sex, age and other demographic data, such as the presence of hypertension, body mass index and form of ventricular involvement. Results: Our main findings were that patients with HCM and a history of paroxysmal AF presented (1) smaller atrial emptying fractions than individuals in the control group; (2) statistically larger atrial volumes in the paroxysmal AF group, with no difference in the diameters of the left atrium (LA). (3) there was a strong reduction of LA strain in overall population, with no difference between groups; (4) and last, active LA emptying fraction was an independent predictor related with the presence of paroxysmal AF (p=0,018; odds ratio=0,93). Conclusions: The measurements of LA emptying fractions by three-dimensional echocardiography, particularly total and active emptying fractions, allowed to differentiate patients with HCM with and without paroxysmal AF. These measures can be a predictor of cardiovascular events and mortality, but mainly, they can be predictors of permanent AF.